Surface impurity removal and regeneration method of waste lithium ion battery positive electrode material
The surface reconstruction and removal of the cathode material of waste lithium-ion batteries is carried out through electrochemical methods, which solves the problem that impurities affect the regeneration effect in the direct recovery method, and achieves uniform regeneration electrochemical performance and efficient lithium element recovery.
Patent Information
- Application Number
- CN202510224846.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-27
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2045-02-27
AI Technical Summary
Among the existing battery recycling methods, especially the direct recycling method, it is difficult to effectively remove impurities on the surface of waste lithium-ion batteries, resulting in uneven regeneration effects and affecting the electrochemical performance of the positive electrode material.
Electrochemical methods are used to remove impurities and regenerate the surface of the positive electrode material of the waste lithium-ion battery. After pretreatment of the waste lithium-ion battery, it is assembled into an electrolytic cell for electrolytic reaction, which promotes the surface reconstruction of the positive electrode material and removes impurities. Finally, the decomposition positive electrode material is obtained through mechanical crushing and organic solvent washing.
It realizes effective decomposition removal of the cathode material of waste lithium-ion batteries, avoids uneven regeneration effects caused by fluorine doping, improves the electrochemical performance of the regenerated cathode material, is suitable for batch recycling and regeneration of different manufacturers, and simplifies the operation process.
Smart Images

Figure CN119725842A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a surface impurity removal and regeneration method for waste lithium ion battery positive electrode materials, belonging to the technical field of battery regeneration. Background Art
[0002] At present, the main battery recycling methods include pyrolysis, wet recycling and direct recycling.
[0003] Regarding pyrometallurgical recycling, despite the continuous improvement of the reaction temperature of recycling, the pyrometallurgical recycling process fundamentally relies on material decomposition and high-temperature melting of elements to form alloys. After pyrometallurgical recycling, mixed slag (usually containing Li, Al, Ca and other elements) will be produced, so this process cannot achieve complete metal element recovery, which ultimately leads to inevitable lithium loss. In order to avoid the waste of important lithium elements, the acid leaching step of the slag is added to separate the metal elements and extract them step by step, but this obviously increases the steps of the entire recycling process. The entire process requires inputs such as high electricity and natural gas to provide high temperature conditions. The input of these components represents an increase in the carbon footprint. Graphite and additional carbon sources need to be added to act as reducing agents to improve efficiency, resulting in a cumbersome and energy-intensive process for pyrometallurgical recycling.
[0004] Regarding wet recovery, first of all, the process usually requires the use of a large amount of chemical reagents, which not only increases costs, but may also cause environmental pollution problems. Secondly, wet recovery has high energy consumption, and the waste liquid and waste gas generated in the process require additional treatment, further increasing environmental pressure. In addition, this method has high equipment requirements and high investment costs. When extracting valuable metals, there may be problems such as low recovery rate and difficulty in completely removing impurities, which affects the purity and quality of the final product. Therefore, although wet recovery is technically mature, its economy and environmental protection still face challenges and urgently need further optimization and improvement.
[0005] Regarding the direct recycling method, for the actual waste lithium-ion battery positive electrode, the impurities on its surface after recycling will greatly affect the effect of direct recycling. During the solid phase regeneration process, the fluoride impurities on the surface will cause the fluorine element to be doped into the positive electrode material, causing unpredictable effects on the positive electrode material. Existing studies have used ammonium fluoride as a fluorinating agent to dope LCO (lithium cobalt oxide), and found that 0.2~0.8% subsurface fluorine doping is beneficial to the lithium ion diffusion of the positive electrode material, but doping above 1% will cause insufficient lithium ion supplementation, leading to the appearance of lithium-deficient spinel phase. Because it is impossible to estimate the actual amount of residual fluorine impurities in waste lithium-ion batteries, direct recycling of waste lithium-ion batteries will lead to unpredictable effects.
[0006] Therefore, in order to solve the problem of large regeneration differences in the direct recycling method, it is necessary to remove the impurities generated during the recycling process of these waste lithium-ion batteries and regenerate normalized positive electrode materials for the sensitive direct recycling process. Summary of the invention
[0007] The purpose of the present invention is to overcome the deficiencies in the prior art, provide a method for surface impurity removal and regeneration of positive electrode materials of waste lithium-ion batteries, use electrochemical methods to solve the impurity problem on the surface of actual waste lithium-ion batteries, and promote direct recovery methods to adapt to the industrial recovery goals of actual waste lithium-ion batteries.
[0008] To achieve the above object, the present invention is implemented by adopting the following technical solutions: In one aspect, the present invention provides a method for removing impurities from the surface of a waste lithium-ion battery positive electrode material, comprising: Pre-treating waste lithium-ion batteries to obtain a positive electrode sheet containing a current collector; Assembling an electrolytic cell with the positive electrode sheet containing the current collector as a working electrode, applying voltage to perform an electrolytic reaction using the electrolytic cell, and during the electrolytic reaction, the positive electrode sheet containing the current collector undergoes surface reconstruction to obtain a reconstructed positive electrode sheet; The polyvinylidene fluoride on the reconstructed positive electrode plate is removed to obtain a positive electrode material with surface impurities removed.
[0009] Further, the waste lithium-ion battery is one or more of a cobalt-acid lithium-ion battery, a lithium iron phosphate lithium-ion battery, a lithium manganese-acid lithium-ion battery, a ternary nickel-cobalt-manganese-acid lithium-ion battery, a ternary nickel-cobalt-aluminum-acid lithium-ion battery, and a quaternary nickel-cobalt-manganese-aluminum lithium-ion battery; The surface impurities of the waste lithium-ion battery include lithium fluoride and transition metal fluoride, and the transition metal oxide includes one or more of cobalt fluoride, nickel fluoride, manganese fluoride, iron fluoride and aluminum fluoride.
[0010] Furthermore, the method of pre-treating waste lithium-ion batteries to obtain a positive electrode sheet containing a current collector comprises: Soak the used lithium-ion battery in a salt solution and discharge it until the discharge termination voltage is 0.5~1.5V; Dismantling discharged waste lithium-ion batteries and cutting the positive electrodes thereof to obtain positive electrode sheets containing current collectors; Wherein, the salt solution adopts a sodium chloride solution with a concentration range of 4-6wt%.
[0011] Furthermore, the counter electrode in the electrolytic cell is one of carbon, graphite, stainless steel, titanium, platinum, gold, silver, lead, conductive glass, etc., and the electrolyte solution is one of the electrolyte solutions that do not contain alkali metal ions.
[0012] Furthermore, the electrolyte solution is an ammonium salt solution, and the ammonium salt solution is one or more of strong acid radical ion ammonium salts (such as ammonium chloride, ammonium nitrate, ammonium sulfate, etc.), weak acid radical ion ammonium salts (such as ammonium sulfate, ammonium bicarbonate, etc.), and organic acid radical ion ammonium salts (ammonium formate, ammonium acetate, ammonium citrate, etc.).
[0013] Furthermore, the voltage is greater than 1 V vs. RHE.
[0014] Furthermore, the method further comprises adding a precipitant to the electrolyte solution after the electrolysis reaction to obtain lithium salt precipitation, wherein the precipitant is a carbonate (such as sodium carbonate, ammonium carbonate, etc.); Furthermore, the removal of polyvinylidene fluoride on the reconstructed positive electrode plate to obtain the surface-decontaminated positive electrode material comprises: mechanically crushing the reconstructed positive electrode plate, collecting the positive electrode material powder or washing and drying it in an organic solvent to obtain the surface-decontaminated positive electrode material; Wherein, the organic solvent is one of N,N-dimethylformamide, N-methylpyrrolidone, N,N-dimethylacetamide and dimethyl sulfoxide.
[0015] On the other hand, the present invention also provides a method for regenerating waste lithium-ion battery positive electrode materials, which comprises the surface impurity removal method of waste lithium-ion battery positive electrode materials described in any one of the above items, and regenerating the positive electrode materials from which the impurities have been removed to obtain regenerated positive electrode materials, wherein the regeneration adopts a solid phase regeneration method or a hydrothermal solid phase regeneration method; The solid phase regeneration method comprises: The positive electrode material with the surface impurities removed is mixed with a lithium source, ground evenly and then calcined to obtain a regenerated positive electrode material; The hydrothermal solid phase regeneration method comprises: The positive electrode material after surface impurities removal is placed in a lithium hydroxide aqueous solution for hydrothermal treatment, washed to neutrality and then dried to obtain a hydrothermal positive electrode material; The hydrothermal positive electrode material is mixed with the lithium source and ground until uniform, and then calcined to obtain a regenerated positive electrode material; Wherein, the lithium source is lithium hydroxide or lithium carbonate.
[0016] Further, the concentration of the lithium hydroxide aqueous solution is 4 mol / L; and / or, the hydrothermal treatment includes hydrothermal treatment at 160-220° C. for a certain time and / or, the calcination includes calcination at 700-1000° C. for 6-24 hours.
[0017] Compared with the prior art, the present invention has the following beneficial effects: The present invention provides an adaptive direct recycling strategy for waste lithium-ion batteries, which induces surface reconstruction of positive electrode materials under weak oxygen evolution potential, promotes self-removal of fluorine impurities, and avoids the phenomenon of uneven regeneration effects between batches caused by impurity-induced fluorine doping in traditional direct recycling methods and the influence of impurities on various properties of regenerated positive electrode materials.
[0018] The recovery method of the present invention does not require the use of strong acids, strong alkalis and a large amount of water, has a simple operation process, and is applicable to batch recovery and regeneration of different batches of the same manufacturer and between different manufacturers, and can achieve uniform regeneration electrochemical performance, thus promoting the industrialization process of direct recovery. At the same time, due to the complete removal of fluorine element, fluorine element can be thoroughly enriched and precipitated in a short time, thus avoiding the damage of fluorine to water bodies during the industrial recovery process, and realizing the sustainable recovery of waste lithium-ion batteries.
[0019] The present invention can avoid to the greatest extent the residual fluorine impurities on the surface of the positive electrode material and the occurrence of bulk fluorine doping caused by the electrolyte remaining on the surface of the waste electrode material and the PVDF not completely removed in the process steps, thereby avoiding the poor regeneration effect caused by impurities and the inability to completely repair the spinel impurity phase. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 This is a schematic diagram of the change in the leaching rate of fluorine element in the surface impurities of waste lithium cobalt oxide over time in Example 1 of the present invention; Figure 2 This is a SEM schematic diagram of the waste lithium cobalt oxide surface reconstruction-induced impurities after removal in Example 1 of the present invention; Figure 3 This is a SEM schematic diagram of waste lithium cobalt oxide after hydrothermal solid phase regeneration in Example 1 of the present invention; Figure 4 This is a TEM schematic diagram of waste lithium cobalt oxide after hydrothermal solid phase regeneration in Example 1 of the present invention; Figure 5 A schematic diagram showing a comparison of the charge and discharge curves of waste lithium cobalt oxide after hydrothermal solid phase regeneration and commercial lithium cobalt oxide in Example 1 of the present invention; Figure 6 This is a schematic diagram of the change in the leaching rate of fluorine element in the surface impurities of waste lithium manganate over time in Example 2 of the present invention; Figure 7 This is a SEM schematic diagram of the waste lithium manganese oxide surface reconstruction-induced impurities removed in Example 2 of the present invention; Figure 8 This is a schematic diagram comparing the charge and discharge curves of waste lithium manganese oxide after solid phase regeneration and commercial lithium manganese oxide in Example 2 of the present invention; Fig. 9 This is a schematic diagram of the change in the leaching rate of fluorine element in the surface impurities of waste lithium iron phosphate over time in Example 3 of the present invention; Fig.10 This is a SEM schematic diagram of waste lithium iron phosphate after surface reconstruction-induced impurities are removed in Example 3 of the present invention; Fig.11 A schematic diagram comparing the charge and discharge curves of waste lithium iron phosphate after solid phase regeneration and commercial lithium iron phosphate in Example 3 of the present invention; Fig.12 This is a schematic diagram of the change in the leaching rate of fluorine element in the surface impurities of waste NMC811 over time in Example 4 of the present invention; Fig.13 This is a SEM schematic diagram of the surface reconstruction-induced impurities of waste NMC811 after removal in Example 4 of the present invention; Fig.14 It is a schematic diagram comparing the charge and discharge curves of waste NMC811 after solid phase regeneration in Example 4 of the present invention and commercial NMC811; Fig.15 This is a schematic diagram of the change in the leaching rate of fluorine element in the surface impurities of waste NMC532 over time in Example 5 of the present invention; Fig.16 This is a SEM schematic diagram of the surface reconstruction-induced impurities of waste NMC532 after removal in Example 5 of the present invention; Fig.17 It is a schematic diagram comparing the charge and discharge curves of waste NMC532 after solid phase regeneration in Example 5 of the present invention and commercial NMC532; Fig.18 Schematic diagram showing the comparison of fluorine content in electrode materials obtained by the regeneration methods of Example 1 of the present invention and Comparative Example 1; Fig.19 A schematic diagram comparing the regenerated electrochemical performance of the electrode materials obtained by the regeneration methods of Example 1 and Comparative Example 1 of the present invention and the electrode materials from different batches of the same manufacturer and different manufacturers; Fig. 20 The present invention is a schematic diagram showing a process comparison between a surface impurity removal and regeneration method for waste lithium-ion battery positive electrode materials and a traditional direct recovery method in an embodiment of the present invention. DETAILED DESCRIPTION
[0021] The present invention will be further described below in conjunction with the accompanying drawings. The following embodiments are only used to more clearly illustrate the technical solution of the present invention, and cannot be used to limit the protection scope of the present invention. Example 1
[0022] The embodiment of the present invention provides a method for removing impurities on the surface of waste cobalt oxide lithium ion batteries and regenerating them by surface reconstruction, which specifically includes: (1) Soaking the waste lithium cobalt oxide battery in a 5wt% NaCl solution until the discharge termination voltage is 1V, and disassembling to obtain a lithium cobalt oxide positive electrode sheet containing a current collector; (2) The lithium cobalt oxide positive electrode was used as the working electrode and the stainless steel mesh was used as the counter electrode. 50 mL of 0.1 mol / L ammonium sulfate aqueous solution was added to the electrolytic cell to assemble the electrolytic cell. A voltage of 1.3 V vs. RHE was applied to the electrolytic cell and the reaction was carried out at room temperature for 5 h.
[0023] (3) After the electrolysis reaction, the lithium cobalt oxide positive electrode sheet is taken out and placed in an N-methylpyrrolidone (NMP) solution for ultrasonic treatment at 60°C for 6 hours. The powder at the bottom is collected, washed, centrifuged and then dried. (4) The powder obtained in step (3) was placed in a hydrothermal reactor, 4 mol / L lithium hydroxide solution was added, and the reaction was carried out at 200°C for 6 hours. The powder at the bottom was collected, centrifuged and washed until neutral, and then dried.
[0024] (5) A certain amount of the powder obtained in step (4) is placed in a mortar, 5% by mass of lithium hydroxide is added, and the mixture is ground and mixed evenly, and then placed in a muffle furnace and calcined at 900° C. for 6 h.
[0025] The leaching amount of fluorine from the surface impurities of the lithium cobalt oxide positive electrode was characterized by ion chromatography, and the reconstruction phenomenon of the surface impurities was characterized by SEM. The regenerated positive electrode material was characterized by scanning electron microscopy (SEM) and transmission electron microscopy (TEM) and the electrochemical performance was tested.
[0026] The fluorine leaching efficiency curve of impurities in the lithium cobalt oxide positive electrode plate after electrolysis in ammonium sulfate solution for 5 hours is as follows Figure 1 As shown, it means that after 5 hours of reaction, the fluoride ion leaching amount reaches the maximum, and the fluorine has been completely leached out.
[0027] SEM images of lithium cobalt oxide after reconstructing during the reaction process Figure 2 As shown, it indicates that flake hydroxides are generated on its surface, indicating the occurrence of reconstruction phenomenon.
[0028] SEM of the cathode material regenerated after the reaction Figure 3 As shown, it is proved that the surface of the regenerated positive electrode material is smooth and no impurity phase remains.
[0029] TEM image of the cathode material regenerated after the reaction Figure 4 As shown, it is proved that the layered peak of the regenerated positive electrode material has good crystallinity, regular lattice fringes and no impurity phases.
[0030] The regenerated positive electrode material and commercially available lithium cobalt oxide were used as positive electrode materials, respectively, and lithium metal was used as the negative electrode. The electrolyte was a carbonate electrolyte with a concentration of 1 M. The solvent was ethylene carbonate (EC), diethyl carbonate (DEC) and dimethyl carbonate (DMC) with a mass ratio of 1:1:1. The solute was LiPF6. They were assembled into button-type lithium-ion batteries in a glove box filled with argon atmosphere (O2 < 0.01 ppm, H2O < 0.01 ppm). The Wuhan Blue Electric Battery Test System was used for constant current charging and discharging. The voltage range of charging and discharging was 3.0 ~ 4.2 V, and the test temperature was a constant temperature of 25 °C. The mass of active materials in the battery used to calculate the specific capacity was calculated based on the mass of the lithium cobalt oxide positive electrode material. The charge and discharge curves of the recycled material are consistent with the charge and discharge curves of the commercial positive electrode material. Figure 5 As shown, it proves its successful regeneration and avoids the influence of impurities on the electrochemical performance. Example 2
[0031] The embodiment of the present invention provides a method for removing impurities on the surface of waste lithium manganese oxide batteries and regenerating them by surface reconstruction, which specifically includes: (1) The waste lithium manganese oxide battery is immersed in a 5wt% NaCl solution until the discharge termination voltage is 1V, and then disassembled to obtain a lithium manganese oxide positive electrode sheet containing a current collector.
[0032] (2) The lithium manganese oxide positive electrode was used as the working electrode and the stainless steel mesh was used as the counter electrode. 50 mL of 0.1 mol / L ammonium sulfate aqueous solution was added to the electrolytic cell to assemble it. A voltage of 1.3 V vs. RHE was applied to the electrolytic cell and the reaction was carried out at room temperature for 5 h.
[0033] (3) After the electrolysis reaction, the lithium manganese oxide positive electrode sheet is taken out, placed in an NMP solution at 60°C for 6 hours, and the powder at the bottom is collected, washed, centrifuged, and then dried; (4) A certain amount of the powder obtained in step (3) is mixed with lithium hydroxide in an equal molar ratio in a mortar, and 10% by mass fraction of lithium hydroxide is additionally added to grind and mix evenly, and then placed in a muffle furnace and calcined at 800° C. for 6 h.
[0034] The leaching amount of fluorine from the surface impurities of lithium manganate was characterized by ion chromatography, the reconstruction phenomenon of the surface impurities was characterized by SEM, and the electrochemical performance of the regenerated positive electrode material was tested.
[0035] The fluorine leaching efficiency curve of impurities in lithium manganese oxide positive electrode after 5 hours of electrolysis in ammonium sulfate solution is as follows: Figure 6 As shown, it means that after 5 hours of reaction, the fluoride ion leaching amount reaches the maximum, and the fluorine has been completely leached out.
[0036] SEM images of the cathode material reconstructed during the reaction process Figure 7As shown, it proves that the positive electrode material has been reconstructed into small particles with no impurities on the surface.
[0037] The regenerated positive electrode material and commercially available lithium manganese oxide were used as positive electrode materials, respectively, and lithium metal was used as the negative electrode. The electrolyte was a carbonate electrolyte with a concentration of 1 M. The solvent was ethylene carbonate (EC), diethyl carbonate (DEC) and dimethyl carbonate (DMC) with a mass ratio of 1:1:1. The solute was LiPF6. They were assembled into button-type lithium-ion batteries in a glove box filled with argon atmosphere (O2 < 0.01 ppm, H2O < 0.01 ppm). The Wuhan Blue Electric Battery Test System was used for constant current charging and discharging. The voltage range of charging and discharging was 3.5~4.3 V, and the test temperature was a constant temperature of 25 °C. The mass of active materials in the battery used to calculate the specific capacity was calculated based on the mass of the lithium manganese oxide positive electrode material. The charge and discharge curves of the recycled material are consistent with the charge and discharge curves of the commercial positive electrode material. Figure 8 , proving its successful regeneration and avoiding the influence of impurities on electrochemical performance. Example 3
[0038] The embodiment of the present invention provides a method for removing impurities on the surface of waste lithium iron phosphate batteries and regenerating them by surface reconstruction, which specifically includes: (1) Soaking the waste lithium iron phosphate battery in a 5wt% NaCl solution until the discharge termination voltage is 1V, and disassembling to obtain a lithium iron phosphate positive electrode sheet containing a current collector; (2) The lithium iron phosphate positive electrode was used as the working electrode and the stainless steel mesh was used as the counter electrode. 50 mL of 0.1 mol / L ammonium sulfate aqueous solution was added to the electrolytic cell to assemble it. A voltage of 1.3 V vs. RHE was applied to the electrolytic cell and the reaction was carried out at room temperature for 5 h.
[0039] (3) After the electrolysis reaction, the lithium iron phosphate positive electrode was taken out and placed in an NMP solution at 60°C for 6 hours, and the powder at the bottom was collected, washed, centrifuged and dried; (4) A certain amount of the powder obtained in step (3) is mixed in a mortar with an equal molar ratio of lithium hydroxide, and 10% by mass of lithium hydroxide and 10% by mass of glucose are additionally added to grind and mix evenly, and then placed in a tube furnace and calcined at 700° C. for 10 h under an argon atmosphere.
[0040] The leaching amount of fluorine from the surface impurities of lithium iron phosphate was characterized by ion chromatography, the reconstruction phenomenon of the surface impurities was characterized by SEM, and the electrochemical performance of the regenerated positive electrode material was tested.
[0041] The fluorine leaching efficiency curve of impurities in lithium iron phosphate positive electrode after electrolysis in ammonium sulfate solution for 5 hours is as follows Fig. 9 As shown, it means that after 5 hours of reaction, the fluoride ion leaching amount reaches the maximum, and the fluorine has been completely leached out.
[0042] SEM images of lithium iron phosphate after reconstructing during the reaction process Fig.10 As shown, it shows that there are broken particles on its surface, indicating the occurrence of reconstruction phenomenon.
[0043] The regenerated positive electrode material and commercially available lithium iron phosphate were used as positive electrode materials, respectively, and lithium metal was used as the negative electrode. The electrolyte was a carbonate electrolyte with a concentration of 1 M. The solvent was ethylene carbonate (EC), diethyl carbonate (DEC) and dimethyl carbonate (DMC) with a mass ratio of 1:1:1. The solute was LiPF6. They were assembled into button-type lithium-ion batteries in a glove box filled with argon atmosphere (O2 < 0.01 ppm, H2O < 0.01 ppm). The Wuhan Blue Electric Battery Test System was used for constant current charging and discharging. The voltage range of charging and discharging was 2.5 ~ 4V, and the test temperature was a constant temperature of 25 °C. The mass of active materials in the battery used to calculate the specific capacity was calculated based on the mass of the lithium iron phosphate positive electrode material. The charge and discharge curves of the recycled material are consistent with the charge and discharge curves of the commercial positive electrode material. Fig.11 , proving its successful regeneration and avoiding the influence of impurities on electrochemical performance. Example 4
[0044] Taking the recycling of NMC811 batteries and NMC532 batteries as an example, this embodiment provides a method for removing impurities on the surface of waste NMC811 batteries and regenerating them by surface reconstruction, specifically including: (1) Soak the used NMC811 battery in a 5wt% NaCl solution until the discharge termination voltage is 1V, and disassemble it to obtain the NMC811 positive electrode sheet containing the current collector; (2) The NMC811 positive electrode was used as the working electrode and the stainless steel mesh was used as the counter electrode. 50 mL of 0.1 mol / L ammonium sulfate aqueous solution was added to the electrolytic cell to assemble it. A voltage of 1.3 V vs. RHE was applied to the electrolytic cell and the reaction was carried out at room temperature for 5 h.
[0045] (3) After the electrolysis reaction, the NMC811 positive electrode was taken out and placed in an NMP solution for ultrasonic treatment at 60°C for 6 h. The powder at the bottom was collected, washed, centrifuged and dried.
[0046] (4) A certain amount of the powder obtained in step (3) is mixed with lithium hydroxide in an equal molar ratio in a mortar, and 5% by mass of lithium hydroxide is additionally added to grind and mix evenly, and then placed in a tube furnace in an oxygen atmosphere at 400°C for 4 hours, and then roasted at 800°C for 6 hours.
[0047] The fluorine leaching amount of NMC811 surface impurities was characterized by ion chromatography, the reconstruction phenomenon of surface impurities was characterized by SEM, and the electrochemical performance of the regenerated positive electrode material was tested.
[0048] The fluorine leaching efficiency curve of impurities in the NMC811 positive electrode after electrolysis in ammonium sulfate solution for 10 hours is as follows Fig.12 As shown in the figure, it shows that after 10 hours of reaction, the fluoride ion leaching amount reaches the maximum, and the fluorine has been completely leached out. Fig.13 As shown, it shows that small particles are generated on its surface, indicating the occurrence of reconstruction phenomenon.
[0049] The regenerated positive electrode material and the commercially available NMC811 were used as positive electrode materials, respectively, and lithium metal was used as the negative electrode. The electrolyte was a carbonate electrolyte with a concentration of 1 M. The solvent was ethylene carbonate (EC), diethyl carbonate (DEC) and dimethyl carbonate (DMC) with a mass ratio of 1:1:1. The solute was LiPF6. They were assembled into button-type lithium-ion batteries in a glove box filled with argon atmosphere (O2 < 0.01 ppm, H2O < 0.01 ppm). The Wuhan Blue Electric Battery Test System was used for constant current charge and discharge. The charge and discharge voltage range was 3.0 ~ 4.2 V, and the test temperature was a constant temperature of 25 °C. The mass of the active material of the battery used to calculate the specific capacity was calculated based on the mass of the nickel-cobalt-manganese ternary positive electrode material. The charge and discharge curves of the recycled material are consistent with the charge and discharge curves of the commercial positive electrode material. Fig.14 , proving its successful regeneration and avoiding the influence of impurities on electrochemical performance. Example 5
[0050] This embodiment provides a method for removing impurities on the surface of waste NMC532 batteries and regenerating them by surface reconstruction, specifically including: (1) Soak the used NMC532 battery in a 5wt% NaCl solution until the discharge termination voltage is 1V, and disassemble it to obtain the NMC532 positive electrode sheet containing the current collector; (2) Place the NMC532 positive electrode in the electrolytic cell as the working electrode and the stainless steel mesh as the counter electrode. Add 50 mL of 0.1 mol / L ammonium sulfate aqueous solution to assemble the electrolytic cell. Apply a voltage of 1.3 V vs. RHE to the electrolytic cell and react at room temperature for 5 h.
[0051] (3) After the electrolysis reaction, the NMC532 positive electrode was taken out and placed in NMP solution at 60°C for 6 h. The powder at the bottom was collected, washed, centrifuged and dried.
[0052] (4) A certain amount of the powder obtained in step (3) is mixed with lithium hydroxide in an equal molar ratio in a mortar, and 5% by mass fraction of lithium hydroxide is additionally added to grind and mix evenly, and the mixture is placed in a tube furnace and calcined at 400° C. for 4 h in an oxygen atmosphere, and then roasted at 800° C. for 6 h in an oxygen atmosphere.
[0053] The fluorine leaching amount of NMC532 surface impurities was characterized by ion chromatography, the reconstruction phenomenon of surface impurities was characterized by SEM, and the electrochemical performance of the regenerated positive electrode material was tested.
[0054] The fluorine leaching efficiency curve of impurities in the NMC532 positive electrode after electrolysis in ammonium sulfate solution for 10 hours is as follows Fig.15 As shown, it means that after 10 hours of reaction, the fluoride ion leaching amount reaches the maximum, and the fluorine has been completely leached out.
[0055] SEM images of NMC532 after reconstructing during the reaction process Fig.16 As shown, it shows that a large number of small particles are generated on its surface, indicating the occurrence of reconstruction phenomenon; the regenerated positive electrode material and the commercial NMC532 are used as positive electrode materials, lithium metal is used as the negative electrode, the electrolyte is a carbonate electrolyte with a concentration of 1 M, the solvent is ethylene carbonate (EC), diethyl carbonate (DEC) and dimethyl carbonate (DMC) with a mass ratio of 1:1:1, and the solute is LiPF6. It is assembled into a button-type lithium-ion battery in a glove box filled with argon atmosphere (O2 <0.01 ppm, H2O <0.01 ppm). The Wuhan Blue Electric Battery Test System is used for constant current charging and discharging. The voltage range of charging and discharging is 3.0 ~4.2 V, and the test temperature is a constant temperature of 25 °C. The mass of active materials of the battery used to calculate the specific capacity is calculated based on the mass of the nickel-cobalt-manganese ternary positive electrode material. The charge and discharge curves of the recycled material are consistent with the charge and discharge curves of the commercial positive electrode material. Fig.17 , proving its successful regeneration and avoiding the influence of impurities on electrochemical performance. Comparative Example 1
[0056] In order to compare the fluorine doping phenomenon produced by the conventional direct regeneration method, the difference between Comparative Example 1 and Example 1 is only that the electrolysis step of step (2) is omitted.
[0057] The hydrothermal solid phase regeneration powder of this comparative example 1 and the hydrothermal solid phase regeneration powder of Example 1 were leached with hydrochloric acid at 50°C for 12 hours and then subjected to ion chromatography test. The results are as follows: Fig.18 As shown, the response of fluorine element is obviously observed in the comparative example 1, while the response of fluorine element is not observed in the embodiment 1, which proves that the fluorine doping phenomenon does not occur in the embodiment 1.
[0058] In order to compare the batch regeneration effects of different recycling methods for waste lithium-ion batteries from different manufacturers, the batteries obtained by the direct recycling method of this comparative example 1 and the batteries obtained by the recycling method of Example 1 were compared in multiple batches for electrochemical performance. Fig.19 As shown, Fig.19 In order to compare the capacities of multiple batches of regenerated batteries, three batches of batteries from the same manufacturer with different production times were selected for regeneration comparison with batteries from four different manufacturers. It can be clearly shown that in the presence of fluorine impurities, the traditional method of comparative example 1 will greatly lead to poor performance or uneven performance of the regenerated batteries, while Example 1 is close to the standard capacity and has good batch-to-batch variability. In view of the industrial recycling environment of waste lithium-ion batteries, it is particularly necessary to remove fluorine impurities, which further highlights the importance of the present invention.
[0059] In summary, the principle of removing impurities on the surface of waste lithium-ion batteries by surface reconstruction in the present invention is as follows: First of all, it is clear that the impurities on the surface of waste lithium-ion batteries include lithium fluoride, transition metal fluorides (including cobalt fluoride, nickel fluoride, manganese fluoride, etc.), fluorine-containing binders such as PVDF, and current collectors. Among them, the role of fluorine-containing binders such as PVDF in lithium-ion batteries is to bond the current collector to the positive electrode sheet; lithium fluoride and transition metal fluorides are all caused by the decomposition of electrolyte on the surface of the positive electrode material of waste lithium-ion batteries during the cycle process.
[0060] Regarding lithium fluoride impurities, under the voltage-driven surface reconstruction reaction of the positive electrode material, the weakly bound lithium fluoride impurities are removed in the form of ions due to the hydrogen-lithium exchange reaction on the surface of the positive electrode material.
[0061] For transition metal fluoride impurities such as cobalt fluoride, due to the high polarity of the transition metal-fluorine bond, during the reconstruction of the positive electrode material, the transition metal-fluorine bond will quickly break to form transition metal ions and fluoride ions. The transition metal ions will quickly combine with the -OH in the solution and precipitate in situ on the surface of the positive electrode material. That is, the transition metal fluoride is reconstructed into the corresponding transition metal hydroxide during the reconstruction of the positive electrode material. This not only avoids the loss of transition metal elements during the recovery process, but also facilitates subsequent regeneration.
[0062] For fluorine-containing binders such as PVDF and current collectors, the volume expansion phenomenon caused by the reconstruction of the positive electrode material causes the adhesion of PVDF and other fluorine-containing binders to decrease, which makes it easier to separate from the positive electrode material, thereby avoiding fluorine doping caused by PVDF residues. At the same time, based on the reconstruction process induced by the electrochemical oxygen evolution reaction, due to the oxygen evolution on the surface of the aluminum foil current collector, the intermolecular force between PVDF and the current collector surface is weakened, so that the current collector is separated from the electrode layer, avoiding aluminum doping in the subsequent regeneration step caused by aluminum residues.
[0063] Combination Fig. 20 This method utilizes the surface reconstruction phenomenon of waste lithium battery positive electrode materials under voltage control to promote the self-removal of impurities on the surface of the positive electrode materials, avoiding the phenomenon of uneven regeneration effects between batches caused by impurity-induced fluorine doping in traditional direct recovery methods. The process does not require the use of strong acids, strong alkalis and large amounts of water, the operation process is simple, and it is suitable for batch recycling and regeneration of different batches from the same manufacturer and between different manufacturers, and can achieve uniform regeneration electrochemical performance.
[0064] The method of the present invention applies the voltage-induced surface reconstruction phenomenon of the positive electrode material to the removal of harmful impurities, avoiding the influence of impurities on the various properties of the regenerated positive electrode material. The method is applicable to almost all commercial positive electrode materials, such as layered LCO, spinel LMO, phosphate olivine LFP, and ternary and quaternary electrode materials, and the recovery rate of lithium and transition metals is close to 100%. For example, for layered LCO positive electrode materials, the method of the present invention can successfully eliminate lithium fluoride impurities on the surface of the positive electrode material, and convert possible cobalt fluoride impurities into hydroxides, and the electrochemical properties of the regenerated positive electrode material are similar to those of commercial positive electrode materials, and are significantly better than the electrochemical properties regenerated by the traditional recycling method. In the comparison of the regeneration effects of waste lithium-ion batteries from different batches of the same manufacturer and different manufacturers, the traditional recycling method shows large batch-to-batch regeneration differences and unstable capacity, and the regenerated positive electrode material obtained by the method of the present invention has small batch-to-batch differences and good regeneration electrochemical properties.
[0065] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the technical principles of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for removing impurities from the surface of waste lithium-ion battery positive electrode materials, characterized in that: include: Pre-treating waste lithium-ion batteries to obtain a positive electrode sheet containing a current collector; Assembling the positive electrode sheet containing the current collector as a working electrode into an electrolytic cell, applying voltage to perform an electrolytic reaction using the electrolytic cell, and during the electrolytic reaction, the positive electrode sheet containing the current collector undergoes surface reconstruction to obtain a reconstructed positive electrode sheet; The polyvinylidene fluoride on the reconstructed positive electrode plate is removed to obtain a positive electrode material with surface impurities removed.
2. The method for removing impurities from the surface of the cathode material of waste lithium-ion batteries according to claim 1, characterized in that: The waste lithium-ion battery is one or more of a cobalt-acid lithium-ion battery, a lithium iron phosphate lithium-ion battery, a lithium manganate lithium-ion battery, a ternary nickel-cobalt-manganate lithium-ion battery, a ternary nickel-cobalt-aluminum lithium-ion battery, and a quaternary nickel-cobalt-manganese-aluminum lithium-ion battery; The surface impurities of the waste lithium-ion battery include lithium fluoride and transition metal fluoride; The transition metal fluoride includes one or more of cobalt fluoride, nickel fluoride, manganese fluoride, aluminum fluoride, and iron fluoride.
3. The method for removing impurities from the surface of the cathode material of waste lithium-ion batteries according to claim 1, characterized in that: The method of obtaining a positive electrode sheet containing a current collector by pre-treating waste lithium-ion batteries comprises: Soak the used lithium-ion battery in a salt solution and discharge it until the discharge termination voltage is 0.5~1.5V; Dismantle the discharged waste lithium-ion batteries, and cut the positive electrodes thereof to obtain positive electrode sheets containing current collectors; Wherein, the salt solution adopts a sodium chloride solution with a concentration range of 4-6wt%.
4. The method for removing impurities from the surface of the cathode material of waste lithium-ion batteries according to claim 1, characterized in that: The counter electrode in the electrolytic cell is one of carbon, graphite, stainless steel, titanium, platinum, gold, silver, lead and conductive glass, and the electrolyte solution is an electrolyte solution free of alkali metal ions.
5. The method for removing impurities from the surface of the cathode material of waste lithium-ion batteries according to claim 4, characterized in that: The electrolyte solution is an ammonium salt solution, and the ammonium salt is one or more of a strong acid ion ammonium salt, a weak acid ion ammonium salt, and an organic acid ion ammonium salt.
6. The method for removing impurities from the surface of the cathode material of waste lithium-ion batteries according to claim 1, characterized in that: The voltage is greater than 1 V vs. RHE.
7. The method for removing impurities from the surface of the cathode material of waste lithium-ion batteries according to claim 1, characterized in that: The method also includes adding a precipitant to the electrolyte solution after the electrolysis reaction to obtain lithium salt precipitation, wherein the precipitant is a carbonate.
8. The method for removing impurities from the surface of the cathode material of waste lithium-ion batteries according to claim 1, characterized in that: The method of removing the polyvinylidene fluoride on the reconstructed positive electrode plate to obtain the positive electrode material with surface impurities removed comprises: mechanically crushing the reconstructed positive electrode plate, collecting the positive electrode material powder or washing and drying the positive electrode material powder in an organic solvent to obtain the positive electrode material with surface impurities removed; Wherein, the organic solvent is one of N,N-dimethylformamide, N-methylpyrrolidone, N,N-dimethylacetamide and dimethyl sulfoxide.
9. A method for regenerating waste lithium-ion battery positive electrode materials, characterized in that: The method comprises the surface impurity removal method of waste lithium-ion battery positive electrode materials according to any one of claims 1 to 8, and regenerating the positive electrode materials from which the surface impurities have been removed to obtain regenerated positive electrode materials, wherein the regeneration adopts a solid phase regeneration method or a hydrothermal solid phase regeneration method; The solid phase regeneration method comprises: The positive electrode material with the surface impurities removed is mixed with a lithium source, ground evenly and then calcined to obtain a regenerated positive electrode material; The hydrothermal solid phase regeneration method comprises: The positive electrode material after surface impurities removal is placed in a lithium hydroxide aqueous solution for hydrothermal treatment, washed to neutrality and then dried to obtain a hydrothermal positive electrode material; The hydrothermal positive electrode material is mixed with the lithium source and ground until uniform, and then calcined to obtain a regenerated positive electrode material; Wherein, the lithium source is lithium hydroxide or lithium carbonate.
10. The method for regenerating the positive electrode material of waste lithium-ion batteries according to claim 9, characterized in that: The concentration of the lithium hydroxide aqueous solution is 4 mol / L; And / or, the hydrothermal treatment includes hydrothermal treatment at 160-220° C. for a certain period of time; And / or, the calcination comprises calcining at 700-1000° C. for 6-24 h.
Citation Information
Patent Citations
Method for recovering lithium from waste ternary lithium batteries
CN110643816A
Electrode material, electrolysis device and application thereof
CN116575063A
Full-chain integrated waste lithium iron phosphate positive plate regeneration method and regenerated lithium iron phosphate positive plate
CN117256066A
Method for recycling metal in positive electrode material of waste lithium ion battery
CN117625968A
Method for preparing ternary positive electrode precursor by recycling waste batteries based on oxygen cathode electrolysis
CN118854304A